Italy is not a good place for men: narratives of places, marriage and masculinity among Malayali migrants - ESTER GALLO (Global Networks, 2006)
Immigration from South Asia to Italy is a recent phenomenon and novel in that the pioneer migrants are often married or single women rather than men. In this article I explore the relationship between a ‘feminization of migration’ and the construction of masculine identities among Malayali migrants from Kerala, South India, who experience migration directly or indirectly through marriages with Malayali women living and working in Rome. The interest in focusing on the relation between women’s pioneer role as migrants and their husbands’ experiences of migration is to show how men’s identity is represented through their conjugal bond with migrant women working in the domestic sector and to understand how masculinity is constructed and contested within and with reference to different places.